Thermally drawn multifunctional fibers: Toward the next generation of information technology - Shen, Yanan; Wang, Zhe; Wang, Zhixun; Wang, Jiajia; Yang, Xiao; Zheng, Xinghua; Chen, Haisheng; Li, Kaiwei; Wei, Lei; Zhang, Ting (InfoMat, 2022)
As the fundamental building block of optical fiber communication technology, thermally drawn optical fibers have fueled the development and prosperity of modern information society. However, the conventional step‐index configured silica optical fibers have scarcely altered since their invention. In recent years, thermally drawn multifunctional fibers have emerged as a new yet promising route to enable unprecedented development in information technology. By adopting the well‐developed preform‐to‐fiber manufacturing technique, a broad range of functional materials can be seamlessly integrated into a single fiber on a kilometer length scale to deliver sophisticated functions. Functions such as photodetection, imaging, acoustoelectric detection, chemical sensing, tactile sensing, biological probing, energy harvesting and storage, data storage, program operation, and information processing on fiber devices. In addition to the original light‐guiding function, these flexible fibers can be woven into fabrics to achieve large‐scale personal health monitoring and interpersonal communication. Thermally drawn multifunctional fibers have opened up a new stage for the next generation of information technology. This review article summarizes an overview of the basic concepts, fabrication processes, and developments of multifunctional fibers. It also highlights the significant progress and future development in information applications. By adopting the well‐developed thermal drawing technique, a broad range of functional materials can be seamlessly integrated into a single fiber on a kilometer length scale to provide more application scenarios. Thermally drawn multifunctional fibers have opened up a new stage for the next generation of information technology. This review article summarizes an overview of the basic concepts, fabrication processes, and developments of multifunctional fibers. It also highlights the significant progress and future development in information applications.